Local Production of Laboratory Mirror and Students’ Achievement in Physics in Abak, Akwa Ibom State, Nigeria - Uboh, Daniel Effiong; Utibe, Uduak James; Abasi, Andrew Umo; Udofia, Sabbath Etim (International Journal of Creativity and Technical Development (IJCTD), 2026)
The study investigates locally produced laboratory mirrors and students’ achievement in Physics in Abak, Akwa Ibom State, Nigeria. A quasi-experimental research design was adopted; the population for the study comprised all Senior Secondary Two Physics students for the year 2024/2025 session in 11 public co-educational Secondary Schools. A sample of 68 SSII students drawn from two schools in their intact classes was used for the study through a purposive sampling technique. The Physics Practical Test was used as an instrument for data collection. It was validated and subjected to reliability analysis. The result showed a reliability coefficient of 0.81 and was deemed appropriate for the main study. Mean, standard deviation, and analysis of covariance were used for data analysis. The results showed that students taught using locally produced and standard laboratory mirrors demonstrated significant achievement in their Physics scores from pre-test to post-test, with the standard laboratory mirror group showing a slightly higher mean difference compared to the local laboratory mirror group. It was recommended that teachers should receive training and support on how to effectively use local and standard laboratory mirrors to improve student achievement in Physics. The researcher hereby concluded that students’ exposure to different instructional materials in learning Physics was found to be most effective in facilitating students’ achievement.